artikel 3 Faktor Penting Yang Mempengaruhi Produktivitas Bongkar Muat Container: 3 Faktor Penting Yang Mempengaruhi Produktivitas Bongkar Muat Container - Fajar, Fajar Transelasi (Cipta Kind Publisher, 2024)
Abstract, There is a decrease in productivity in loading and unloading containers at Tanjung Emas Port, Semarang. In literature research on transportation management, this article analyzes loading and unloading labor, equipment and meters that influence container loading and unloading performance. Building a hypothesis of influence between variables is the aim of this paper. The results of this literature research are as follows: 1) Labor influences the productivity of loading and unloading containers; 2) Equipment influences the productivity of loading and unloading containers; and 3) Kade Meter influences the Productivity of Container Loading and Unloading. Keywords: Literature Review, Tanjung Emas, Productivity